Decorin promotes apoptosis and autophagy via suppressing c-Met in HTR-8 trophoblasts. Issue 6 (May 2020) - Wang, Yeping; Zhang, Hongping; Zhang, Yuehui; Li, Xiaoqing; Hu, Xianqing; Wang, Xietong
Abstract : Decorin (DCN) regulates a vast array of cellular processes including proliferation, migration, apoptosis, and autophagy, and its aberrant expression has been associated with poor extravillous trophoblasts (EVT) invasion of the uterus, which underlies the occurrence of preeclampsia (PE) and intrauterine growth restriction (IUGR). In this study, we aim to elucidate the molecular mechanism of how the DCN regulates the cell functions through the use of trophoblast cell line, HTR-8. Using a series of cell function assays, including CCK8, RTCA, transwell, scratch-wound assay, and Annexin V staining, we found that DCN suppressed proliferation and invasion, while promoted autophagy and apoptosis of HTR-8 in a dose-dependent manner. Transient stimulation of DCN have increased the activity of c-Met and its downstream effectors – Akt, FAK and m-TOR. However, a prolonged exposure to DCN have significantly downregulated the expression of c-Met, leading to suppression of its downstream effectors. Lentivirus that overexpressed c-Met targeting shRNA was used to knockdown c-Met expression and crizotinib was used to selectively inhibit the kinase activity of c-Met in HTR-8 cells. A combination of DCN and c-Met knockdown/inhibition have reduced the proliferation and invasion in HTR-8 cells; however, DCN-induced autophagy and apoptosis were not synergistically enhanced by c-Met inhibition. In conclusion, DCN promotes autophagy and apoptosis predominantly through downregulating c-Met/Akt/mTOR activity in human trophoblasts.